Contribution of Work Motivation, Compensation, and Work System to Employee Performance Improvement at LPPOM MUI DKI Jakarta - Farrah, Intan; Putri, Elsa Asrina; Syahyanti, Oktrina; Vadila, Fetry; Pranata, Joko; Nasti, Nilawati (Mahesa Research Center, 2025)
This study aims to analyze the contribution of work motivation, compensation, and work system to employee performance improvement at LPPOM MUI DKI Jakarta. The research uses a quantitative approach with a survey method, where data is collected through a questionnaire filled out by 35 respondents. The analysis technique used was multiple linear regression to test the influence of the three independent variables (work motivation, compensation, and work system) on the dependent variable (employee performance). The results of the study show that work motivation, compensation, and work system significantly have a positive effect on employee performance. Work systems have the greatest influence, with a regression coefficient of 0.412, followed by work motivation (0.348) and compensation (0.263). The Adjusted R2 value of 0.564 shows that these three variables explain 56.4% of the variability of employee performance. This study concludes that to improve employee performance, LPPOM MUI DKI Jakarta needs to improve the work system, as well as maintain adequate levels of motivation and compensation. These findings are also in line with human resource management theory which states that motivation, rewards, and a supportive work environment are key factors in driving employee productivity.